RELATIONSHIP BETWEEN VOLTAGE AND STRONG ELECTRIC CURRENT ON 1.5 VOLT BATTERIES WITH ADDING CASSAVA LEAVES - ety jumiati; abdul halim daulay; asnitha aritonang (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Biobattery research has been carried out using cassava leaves (Manihot Utilissima) as a substitute for carbon in some 1.5 volt batteries. And tested the voltage with the results of sample A: 1.53 volts; B: 1.54 volts; C: 1.55 volts; and D: 1.58 volts. Then the electric current was also tested with the values obtained in sample A: 0.08 mA; B: 0.10 mA; C: 0.13 mA; and D: 0.19 mA. If the carbon mass in the biobattery gets higher, the value of the voltage and electric current test results changes with the higher in each sample. By performing the performance on the cassava leaf biobattery, it is able to turn on a 2.5 watt LED lamp with 3 batteries. Keywords: Current, cassava leaves, and voltage